Sulphur Supply Enhances Wheat Growth and Yield on Saline-Sodic Soil: Wheat Growth in Saline-Sodic Soil - Arshadullah, Muhammad; Hyder, Syed Ishtiaq; Ali, Arshad (Biological Sciences - PJSIR, 2011)
. The effect of different S levels (0, 25, 50 and 75 kg S/ha) on growth and ionic concentration of wheat variety Inqlab-91 directly sown on saline-sodic soil (ECe=5.65 dS/m, pH=8.57 and SAR=17.38) was evaluated in a field experiment. Treatments were arranged using randomized complete block design (RCBD) with three replications. The crop was harvested at maturity, data on tillering, plant height, spike length, number of grains/spike, 1000- grain weight and yields (grain and straw) were recorded. Na, K, Ca and S concentrations in grain and straw were estimated using atomic absorption spectroscopy. Tillering, number of grains/spike, 1000- grain weight and grain yield significantly (p :: 0.05) increased by enhancing the S application. Maximum wheat yield (4.66 t/ha) was recorded when S was applied at 75 kg/ha, which was 43% more than the control treatment. Maximum number of tillers/plant (161) and number of grains/spike (56) were recorded with sulphur applied at 75 kg/ha. Positive correlation (r = 0.85), (r = 0.88) between calcium, potassium and negative correlation (r = -0.84) between grain sodium content and wheat grain yield was recorded. It indicates that presence of significantly higher Ca and K contents of grain receiving S application might possibly help plants to attain more Ca and K and avoided sodium uptake to alleviate salinity/sodicity stress. Economical analysis showed that maximum value cost ratio (5.5:1) was achieved with the application of 25 kg S/ha.